Toward a Classification of Juvenile Offenders: Subgroups of Serious Juvenile Offenders and Severity of Recidivism - Mulder, Eva (International journal of offender therapy and comparative criminology, 2019)
The aim of this study was to identify subgroups of serious juvenile offenders on the basis of their risk profiles, using a data-driven approach. The sample consists of 1,147 of the top 5% most serious juvenile offenders in the Netherlands. A part of the sample, 728 juvenile offenders who had been released from the institution for at least 2 years, was included in analyses on recidivism and the prediction of recidivism. Six subgroups of serious juvenile offenders were identified with cluster analysis on the basis of their scores on 70 static and dynamic risk factors: Cluster 1, antisocial identity; Cluster 2, frequent offenders; Cluster 3, flat profile; Cluster 4, sexual problems and weak social identity; Cluster 5, sexual problems; and Cluster 6, problematic family background. Clusters 4 and 5 are the most serious offenders before treatment, committing mainly sex offences. However, they have significantly lower rates of recidivism than the other four groups. For each of the six clusters, a unique set of risk factors was found to predict severity of recidivism. The results suggest that intervention should aim at different risk factors for each subgroup.